Physicochemical Characteristics of Nata De Banana Produced From Ambon Banana Peels (Musa paradisiaca L.) Cultivated in The Highlands and Lowlands of Bengkulu Province, Indonesia - Dewi Jumiarni; Getteri Hulandari; Irwandi Ansori (CV Media Inti Teknologi, 2026)
Background: Banana peel waste from Ambon bananas contains essential nutrients that support the growth of Acetobacter xylinum in nata production. Differences in cultivation environments, such as highland and lowland areas, may influence the composition of banana peels and subsequently affect the characteristics of nata de banana produced. Aims: This study aimed to analyze the differences in characteristics of nata de banana produced from Ambon banana peels cultivated in highland and lowland areas, focusing on physical properties and sensory acceptance. Methods: An experimental design was used with banana peels from highland and lowland areas as the differentiating variables. Data on nata characteristics were analyzed statistically using an independent sample t-test with SPSS version 23. Result: The results showed significant differences in thickness and weight of nata de banana between the two sources. Nata produced from highland banana peel extract had greater thickness and weight. Organoleptic tests also indicated that nata from highland peels was more preferred in terms of color, texture, taste, and aroma. Conclusion: Ambon banana peels from highland areas demonstrate higher potential as raw material for nata production, offering an effective approach to utilizing local natural resources and improving the management of banana peel waste.